Non-tuberculous mycobacteria in end stage cystic fibrosis: implications for lung transplantation. Issue 6 (6th April 2006) - Chalermskulrat, W; Sood, N; Neuringer, I P; Hecker, T M; Chang, L; Rivera, M P; Paradowski, L J; Aris, R M
Abstract : Background: WC and NS contributed equally. Non-tuberculous mycobacteria (NTM) frequently colonise patients with end stage cystic fibrosis (CF), but its impact on the course of the disease following lung transplantation is unknown. Methods: Lung transplant recipients with CF who underwent lung transplantation at our institution between January 1990 and May 2003 (n = 146) and CF patients awaiting lung transplantation in May 2003 (n = 31) were studied retrospectively. Results: The prevalence rate of NTM isolated from respiratory cultures in patients with end stage CF referred for lung transplantation was 19.7%, compared with a prevalence rate of 13.7% for NTM isolates in CF lung transplant recipients. The overall prevalence of invasive NTM disease after lung transplantation was low (3.4%) and was predicted most strongly by pre-transplant NTM isolation (p = 0.001, Fisher's exact test, odds ratio (OR) 6.13, 95% CI 3.2 to 11.4). This association was restricted to Mycobacterium abscessus (p = 0.005, Fisher's exact test, OR 7.45, 95% CI 2.9 to 16.9). While NTM disease caused significant morbidity in a small number of patients after transplantation, it was successfully treated and did not influence the post-transplant course of the disease. Conclusion: The isolation of NTM before transplantation in CF patients should not be an exclusion criterion for lung transplantation, but it may alert the clinician to patients at risk of recurrence following transplantation.